USER ACCEPTANCE TESTING (UAT) PADA ELECTRONIC DATA PREPROCESSING GUNA MENGETAHUI KUALITAS SISTEM - Wulandari, Wulandari; Nofiyani, Nofiyani; Hasugian, Humisar (Jurnal Mahasiswa Ilmu Komputer, 2023)
A system is considered qualified if the system built satisfies and provides convenience for its users. The quality of the system can be determined by testing the system with a measured value UAT (User Acceptance Test) is the method used to measure system quality. The current problem is that the data obtained in the mining process is not in ideal conditions, this is because the data format does not meet the requirements, thus hindering the text mining process. This study aims to determine the quality of the Electronic Data Preprocessing system that has been built. The development of this system aims to facilitate pre-processing activities before being used for text mining, making it easier for users to use raw data into ready-to-use data. The test in this study was the User Acceptance Test (UAT) using ISO 9126 dimensions and the scale used was the Likert scale. The test tested the functionality, reliability, usability, and efficiency of the system. The results obtained were questionnaires filled in by respondents with positive to negative gradation options, namely very good, good, sufficient, not good and not good. The test results of the system have fulfilled the standard requirements of ISO 9126 with a functionality characteristic of 86.00% (Very Good), a reliability characteristic of 79.20% (Good), a usability characteristic of 84.25% (Good), an efficiency characteristic of 92.00 %(Very Good), and 84.80%(Very Good) Recapitulation characteristics.